The Effect of Employee Experience on Adaptability to Technological Change of Automotive Employees with Gender as Moderation at PT. Marugo Rubber Indonesia - Syifa Edenia; Mohammad Darul Fadli, Uus; Ery, Rosmawati; Prayudo, Gito (Research in Management of Technology and Business, 2025)
This study aims to analyze the influence of Employee Experience on employee adaptability to technological change at PT Marugo Rubber Indonesia, and evaluate the role of gender as a moderating variable. The results show that Employee Experience contributes significantly by 81.3% to Adaptability to Technological Change. The main indicators that influence Employee Experience are digital culture and work practices (outer loading = 0.916), while emotional stability is a key dimension in Adaptability (outer loading = 0.827). Analysis using SmartPLS 4 shows that gender does not have a significant effect in moderating the relationship between Employee Experience and Adaptability. This study uses a quantitative method with 100 employee respondents, selected based on proportional sampling techniques. These findings emphasize the importance of investing in a digital work culture, technology-based training, and a supportive work environment to improve employee adaptability to technological change. The study results are expected to be a strategic guide for companies in managing human resources to increase productivity, effectiveness, and competitiveness in the digital transformation era.